Improvement of Dissolution Characteristics of Edoxaban through Solid Dispersion Technique - Rasika R. Giri (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: This study aimed to identify the most effective carrier system for enhancing the solubility of Edoxaban (EDO) through the preparation of solid dispersions (SDs) using a novel microwave-induced fusion technique. Materials and Methods: Various carriers including PEGs (3350–20000), PVPs (K-12–K-90), Poloxamers (108–407), and urea were employed to prepare SDs of EDO. Drug–carrier compatibility was assessed, followed by evaluation of SD flow properties. SDs were compressed into tablets and analyzed for physicochemical parameters such as thickness, hardness, friability, drug content, solubility, and in vitro dissolution. A high-performance liquid chromatography method was developed to quantify drug release. Results: Among all carriers, a blend of PEG-8000, PVP-K-30, and Poloxamer 188 showed the best enhancement in EDO solubility and dissolution rate. The optimized formulation exhibited superior physical tablet properties and content uniformity. Accelerated stability studies confirmed formulation robustness. In vivo release studies and pharmacokinetic comparisons with a marketed product confirmed enhanced bioavailability. Conclusion: The combination of PEG-8000, PVP-K-30, and Poloxamer 188 in microwaveinduced SDs significantly improved the solubility and performance of EDO, demonstrating a promising strategy for enhancing poorly soluble drugs.